Peran Resiliensi dan Secure Attachment terhadap Orientasi Masa Depan pada Remaja di Lembaga Kesejahteraan Sosial Anak - Muhibbin, Maulana Arif; Sari, Anggraeni Swastika; Deanova, Ikbar Ihza; Hakiki, Rizky Akbar Putra; Maulana, Mochammad Arif Hadi (Universitas Muhammadiyah Metro, 2024)
Without parental direction, adolescents living in orphanages face difficulties deciding about their future orientation in careers and educational paths. Therefore, to effectively support them, protective factors must be identified. This study aims to examine the effect of resilience and secure attachment on how adolescents living in orphanages see their future orientation in relation to their education and careers. Purposive sampling strategies were used to select 96 teenagers from orphanages as research subjects. In this study, three measuring devices were employed. The Secure Attachment variable was measured using the attachment model of Bartholomew & Horowitz (1991), the future orientation variable was measured using the Future Expectation Scale of Adolescents (Dwiastuti dkk.,2023), and the resilience variable was measured using the seven aspects of resilience according to Reivich & Shatte (2002). The analysis was carried out utilizing multiple regression. The results of the hypothesis show that resilience and stable attachment play a crucial role in the future orientation of teenagers in foster care. This is supported by the values p=0.004 (p<0.05), R=0.335, R Square=0.093, and F=5.893. Thus, it can be concluded that the resilience and secure attachment variables, when combined, contribute an effective 9% to increasing the quality of future orientation in education and career fields for adolescents living in orphanages.